Pengembangan ERP Untuk Digitalisasi Proses Produksi dan Penjualan Pupuk - Aries Alfian Prasetyo; Laily Ulfiyah; Achmad Afandi; Andhi Setiawan; Muhammad Jauhar Vikri (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
Competition in the industrial world after the impact of Covid-19 has become fierce competition. Many companies choose to increase effectiveness and efficiency by implementing digitalization in production and sales activities. PT. Megarhizo Ega Persada is a company that is developing, a company whose main production is liquid organic fertilizer under the brand "Megarhizo". Production activities still use manual bookkeeping processes. So it takes a long time for distribution from the warehouse to the production location. Miscalculations often occur in warehouses resulting in inappropriate production targets, due to insufficient or expired materials due to being in the warehouse for too long. This problem often occurs because the recording process is not thorough and results in stock buildup or stock shortages in the warehouse. So we need a system that can easily and quickly manage data so that these things don't happen again. Digitalization of the sales process is a solution to this problem, fertilizer products are products that are different from other production, because fertilizer is a product that is monitored so the price of fertilizer should not burden the public. By digitizing sales, companies can directly monitor stock and products sold from each distribution location to the resellers. So the number of products sold and prices can still be monitored, besides that the company can also find out the effectiveness of fertilizer production.